Enhancing care service utilization and reducing burden: the role of needs assessments for dementia caregivers in long-term care - Yung-Yu Su; Wen-Fu Wang; Kai-Ming Jhang; Lih-Wen Mau; Chun-Min Chen (BMC Nursing)
Abstract Background Informal caregivers of people living with dementia often face significant physical and psychological burdens, which may limit their utilization of available support services. Needs assessments aim to identify these stressors and facilitate access to supportive resources. This study evaluates the effectiveness of needs assessments in enhancing service utilization and reducing the burden among informal caregivers of people living with dementia in central Taiwan. Methods A retrospective cohort study was conducted involving 464 informal caregivers of people living with dementia in central Taiwan, with data collected from January 2020 to December 2021. The primary outcome, caregiver burden, was assessed using the Zarit Burden Interview (ZBI) at the initial needs assessment (Time 1) and six months post-assessment (Time 2). Data on other variables, including service utilization, were collected at baseline, Time 1, and Time 2 through structured questionnaires. Linear regression analyses examined the relationships between caregiver burden, service utilization, and influencing factors. Results The implementation of needs assessments was associated with increased long-term care (LTC) service utilization. The proportion of caregivers using services rose from 37.3% at baseline to 45.5% after six months. The caregiver burden distribution shifted, with a reduction in moderate to severe burden (from 20.4 to 17.8%) and a slight increase in mild to moderate burden (from 43.7 to 47.2%). Linear regression analysis revealed several key factors influencing caregiver burden. Supportive resources were significantly associated with lower Zarit Burden Interview (ZBI) scores, an effect that often strengthened over time. Specifically, enhanced self-care abilities and the involvement of a foreign caregiver significantly reduced burden at both Time 1 (B = -4.79 and B = -5.44, respectively) and Time 2(B = -6.63 and B = -6.78, respectively). The positive impact of shared caregiving responsibilities became statistically significant at Time 2 mark (B = -5.86). Conversely, initial stressors were linked to higher burden. Caregiving for individuals with severe disabilities (B = 3.31) and the need to manage barrier-free environments (B = 5.06) were associated with greater burden at Time 1, though their influence diminished over time. Emotional strain was a strong predictor of increased burden at both time points (B = 3.51 at Time 1; B = 2.93 at Time 2), although its impact also lessened. Finally, older caregiver age was correlated with a lower burden at both time points. Conclusions The findings highlight the effectiveness of needs assessments in reducing caregiver burden and enhancing service utilization. Needs assessments play a critical role in identifying caregiver stressors and facilitating targeted interventions, essential for sustainable long-term care and caregiver well-being.